Lipidome remodeling activities of DPA-EA in palmitic acid-stimulated HepG2 cells and the in vivo anti-obesity effect of the DPA-EA and DHA-EA mixture prepared from algae oil - Fang, Hua; Cao, Yin; Zhang, Jianyu; Wang, Xiumei; Li, Mengyu; Hong, Zhuan; Wu, Zhen; Fang, Meijuan (Frontiers in Pharmacology, 2023)
Background: The nuclear receptor Nur77 has been demonstrated to play a vital role in the inflammatory response and cellular metabolisms, and its ligands exhibit efficacy in the treatment of inflammation-related diseases (e.g., improving mouse acute lung injury (ALI) and obesity. Recently, ω-3 polyunsaturated fatty acid-ethanolamine derivatives (ω-3 PUFA-EAs), including DPA-EA and DHA-EA, have been reported as new Nur77-targeting anti-inflammatory agents. However, the lipid-lowering effect of ω-3 PUFA-EAs is still unknown, and lipid profile changes induced by Nur77-targeting anti-inflammatory agents also remain unclear. Objective: This study aimed to evaluate the lipid-lowering effect and the underlying mechanism of DPA-EA acting as Nur77-targeting anti-inflammatory agents. It also aimed to investigate the in vitro and in vivo lipid-lowering effects of the DPA-EA and DHA-EA mixture prepared from algae oil. Methods: The in vitro lipid-lowing effect of DPA-EA and its mixture with DHA-EA was first evaluated in palmitic acid-stimulated HepG2 Cells. To confirm the lipid-lowering effect and explore the underlying mechanism, we performed untargeted lipidomic analysis using ultra-performance liquid chromatography/triple quadrupole-time-of-flight (TOF) mass spectrometry coupled with multivariate statistical analysis, with another Nur77-targeting anti-inflammatory compound Celastrol (Cel) as a reference. Finally, we examined the anti-obesity effect of the DPA-EA and DHA-EA mixture synthesized from algae oil in a high-fat diet (HFD)-fed mice model. Results: DPA-EA significantly alleviated lipid accumulation with lower toxicity than Celastrol. Nur77-targeting compounds DPA-EA and Celastrol could simultaneously reduce 14 lipids (9 TGs, 2 PCs, 1 PA, 1 SM, and 1 LacCer) and increase 13 lipids (4 DGs, 6 LPEs, 2 PEs, and 1PC) in Pal-stimulated HepG2 cells. However, Cer lipids were more sensitive to DPA-EA, while the over-downregulation of SM lipids might be associated with the off-target toxicity of Celastrol. The mixture of DPA-EA and DHA-EA synthesized from algae oil could significantly decrease TG, TC, and LDL levels and increase HDL levels in HFD-fed mice, exerting an excellent anti-obesity effect. Conclusion: Nur77-targeting anti-inflammatory compound DAP-EA could promote the hydrolysis of PEs and TGs to ameliorate lipid accumulation. The DPA-EA and DHA-EA mixture prepared from algae oil might be a potential therapeutic agent for obesity and other inflammation-related diseases.